2009
DOI: 10.1017/s0022112009007241
|View full text |Cite
|
Sign up to set email alerts
|

Global stability of flow past a cylinder with centreline symmetry

Abstract: Global absolute and convective stability analysis of flow past a circular cylinder with symmetry conditions imposed along the centreline of the flow field is carried out. A stabilized finite element formulation is used to solve the eigenvalue problem resulting from the linearized perturbation equation. All the computations carried out are in two dimensions. It is found that, compared to the unrestricted flow, the symmetry conditions lead to a significant delay in the onset of absolute as well as convective ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
(82 reference statements)
1
9
0
Order By: Relevance
“…In addition, centreline perturbation velocities for the OE modes are significantly increased with increasing blockage. Kumar et al (2009) have suggested that this non-monotonic variation is because of the effect of the lateral boundaries in suppressing disturbance growth in the cross-stream direction, together with the effect of local flow acceleration in the streamwise direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, centreline perturbation velocities for the OE modes are significantly increased with increasing blockage. Kumar et al (2009) have suggested that this non-monotonic variation is because of the effect of the lateral boundaries in suppressing disturbance growth in the cross-stream direction, together with the effect of local flow acceleration in the streamwise direction.…”
Section: Discussionmentioning
confidence: 99%
“…In Jackson (1987), the finite element method was used to solve an extended set of equations for detecting Hopf bifurcation for a class of bluff bodies. The global stability approach has also been used by Morzyński & Thiele (1991), Morzyński, Afanasiev & Thiele (1999), Chen, Pritchard & Tavener (1995), Kumar & Mittal (2006), Mittal, Kottaram & Kumar (2008), Kumar et al (2009) amongst others, for discussing the instability of the flow past cylinders and related problems. Morzyński et al (1999) was one of the first papers to suggest the use of subspace iteration (see Saad 1989) for solving the eigenvalue problem of the type arising in hydrodynamic stability computations using the global stability approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, variations of the Stuart-Landau equation have been used by Noack et al (2003), Sipp & Lebedev (2007), and Sengupta et al (2010) to model the spatial and temporal evolution of flow instabilities. Other modern advancements in stability analysis of two-dimensional incompressible flow around a circular cylinder include the experimental determination of σ r (Strykowski & Sreenivasan 1990), the location of both the instability core and regions of high sensitivity to perturbations (Giannetti & Luchini 2007), and the isolation of the antisymmetric modes that give rise to further instabilities at higher Re (Kumar et al 2009). As can be seen from the above discussion, the wake geometry at stable Re, the transient behaviour of the flow as it transitions from a steady closed wake to a two-dimensional vortex street, and the fully-developed laminar vortex street have been investigated quite extensively for incompressible flow.…”
Section: Introductionmentioning
confidence: 99%
“…Because the end of a steady RR is a stagnation point, a small vertical plate at this location will have very little effect on the flow, apart from being highly effective in suppressing this particular mode [43]. However, such 'passive' flow control approaches will be unable to control subsequent instability modes (with the initial laminar ones analysed in [44]). Flow past a two-dimensional cylinder and over backwards steps have served as test problems for several active flow control strategies, both for the finite-Re case [45,46] and for Euler (point vortex) flows [47].…”
Section: (D) Time Instabilities and Flow Controlmentioning
confidence: 99%